2017
DOI: 10.1016/j.injury.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Systemic anticoagulation in the setting of vascular extremity trauma

Abstract: In this multicenter prospective cohort, intraoperative systemic anticoagulation was not associated with a difference in rate of repair thrombosis or limb loss; but was associated with an increase in blood product requirements and prolonged hospital stay. Our data suggest there is no significant difference in outcome to support use of ISA for repair of traumatic arterial injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Similarly, Guerrero et al and Maher et al showed anticoagulation improved limb salvage in patients who present with arterial injuries in the common iliac and popliteal arteries who then underwent operative intervention [21,25]. Furthermore, patients who were administered ISA had a decreased return to the [26] ISA and post operative VTE No distinction Maher et al [27] ISA Arterial patency Upper and lower Humphries et al [29] ISA Amputation and repair failure No distinction Wang et al [24] ISA/ILA and post operative Amputation, arterial patency, VTE No distinction Guerrero et al [23] ISA/recovery room Amputation Lower Melton et al [25] ISA Amputation Lower Wagner et al [22] ISA Amputation Lower operating theatre for post-operative bleeding and were significantly more likely to maintain arterial patency, in addition to requiring a shorter Intensive Care Unit and overall stay in the hospital [25]. Conversely, ISA in patients with major vascular injury of the neck, torso or proximal upper (to the elbow), and lower (to the knee) extremities was shown to reduce the incidence of VTE and subsequent post-operative addition of enoxaparin prophylaxis also reduced VTE incidence [24].…”
Section: Studies Demonstrating Positive Outcomesmentioning
confidence: 90%
See 4 more Smart Citations
“…Similarly, Guerrero et al and Maher et al showed anticoagulation improved limb salvage in patients who present with arterial injuries in the common iliac and popliteal arteries who then underwent operative intervention [21,25]. Furthermore, patients who were administered ISA had a decreased return to the [26] ISA and post operative VTE No distinction Maher et al [27] ISA Arterial patency Upper and lower Humphries et al [29] ISA Amputation and repair failure No distinction Wang et al [24] ISA/ILA and post operative Amputation, arterial patency, VTE No distinction Guerrero et al [23] ISA/recovery room Amputation Lower Melton et al [25] ISA Amputation Lower Wagner et al [22] ISA Amputation Lower operating theatre for post-operative bleeding and were significantly more likely to maintain arterial patency, in addition to requiring a shorter Intensive Care Unit and overall stay in the hospital [25]. Conversely, ISA in patients with major vascular injury of the neck, torso or proximal upper (to the elbow), and lower (to the knee) extremities was shown to reduce the incidence of VTE and subsequent post-operative addition of enoxaparin prophylaxis also reduced VTE incidence [24].…”
Section: Studies Demonstrating Positive Outcomesmentioning
confidence: 90%
“…Moreover, the studies looked at a range of different locations that were affected by the trauma. There were 4 studies that exclusively looked at lower limb trauma [20][21][22][23] whilst 3 looked at both upper and lower [24][25][26]. However, one study did not make clear distinctions between anatomical locations of the traumatic insult [27].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations